Testing the significance of pricing factors of oil and gas companies. - Antonio Garcia-Amate; Laura Molero-González; Miguel Angel Sánchez-Granero; Juan Evangelista Trinidad-Segovia; Andres García-Medina (PLoS ONE)
For decades, fossil fuels have accounted for 70% to 80% of global primary energy demand. Far from ending this trend, O&G companies continue to be the main fore-runners in providing secure, versatile and widespread energy to the entire world. The relevance of this sector in the economic-financial landscape and the concern for its stability, makes that the high interest of the scientific community to explore the factors that explain the O&G cross-sectional expected returns remains intact. Through a new approach from the Random Matrix Theory, the aim is to know how many are the factors that explain the market performance of the O&G subsectors (upstream, midstream & downstream), and also if the Brent price can be considered an explanatory factor. We will show that for certain periods, Brent becomes the only factor explaining the movements in the upstream and midstream subsectors, while for most of the time the only factor is the market. Other interesting finding is that no significant factors are found for the downstream subsector, except in certain periods. With a purely statistical approach, we show the factors that explain the cross-sectional expected return of the O&G companies, providing information of special relevance for the decision making of investors, executives and politicians.